A Laboratory of Stories: Teaching and Learning through Community Lore in the Contemporary Esoteric Society Sodalitas Rosae Crucis - Cejvan, Olivia (Approaching Religion, 2024)
This article develops the concept of community lore, initially devised by the social learning theorists Jean Lave and Etienne Wenger (1991). In extending this promising but hitherto neglected aspect of their work, this article sheds light on how and why community lore sustains and propels teaching and learning in the contemporary esoteric society Sodalitas Rosae Crucis (SRC). Ethnographic findings illuminate how the situated, informal community lore becomes a pervasive learning device that underwrites individual and collective learning, as it emerges in small talk, gossip, and cautionary tales, told and shared among members. Furthermore, a dynamic of tradition and innovation is at play within the community lore, as it sustains tradition while also providing a breeding ground for new ideas and practices that lead to innovation. Within the constructive tension between tradition and innovation, I delineate how community lore works as an educational resource, with explanatory value for situated learning, especially within esoteric communities of practice.